Empirical Analysis of the Impact of Brexit Referendum and Post-Referendum Events on Selected Stock Exchange Indexes - Kurecic Petar (South East European Journal of Economics and Business, 2018)
The paper studies the impact of political turbulence in the United Kingdom in 2016 and 2017 on selected relevant stock indexes. The empirical analysis consists of unit breakpoint tests. The potential points of structural break are determined based on an overview of occurrences of political instability from the Brexit referendum to the snap Parliamentary election of 2017. The paper concludes that the outcome of the referendum on Brexit caused a structural break that was visible in every stock index studied. On the other hand, the paper fails to find any evidence of a structural break caused by subsequent events, namely the decision to call the snap election or the outcome of the election itself. This implies that investors have accepted the UK decision to leave the EU and there was no further destabilization of the stock markets. It can be further concluded that the United Kingdom and the European Union need to address a deep political divide and find a way to coexist and mutually benefit in the period of negotiations and after the Brexit takes place